THE GREAT GAME BETWEEN THE BRITISH AND RUSSIAN EMPIRES IN THE 19TH CENTURY: A HISTORICAL ANALYSIS - Xudoyberdiyev Otabek Zafar o'g'li (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Annotation: This article presents a historical analysis of The Great Game—the strategic rivalry and political confrontation between the British and Russian Empires during the 19th century over influence in Central Asia. The study explores the geopolitical motivations behind the imperial expansion of both powers, key events and figures involved, and the implications of their rivalry on the region's political, social, and territorial landscape. By examining archival sources and historiographical debates, the article aims to provide a comprehensive understanding of how the Great Game shaped regional dynamics and contributed to the modern political geography of Central Asia.